The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1038/s41396-021-00995-x
|View full text |Cite
|
Sign up to set email alerts
|

Genomic evolution of the class Acidithiobacillia: deep-branching Proteobacteria living in extreme acidic conditions

Abstract: Members of the genus Acidithiobacillus, now ranked within the class Acidithiobacillia, are model bacteria for the study of chemolithotrophic energy conversion under extreme conditions. Knowledge of the genomic and taxonomic diversity of Acidithiobacillia is still limited. Here, we present a systematic analysis of nearly 100 genomes from the class sampled from a wide range of habitats. Some of these genomes are new and others have been reclassified on the basis of advanced genomic analysis, thus defining 19 Aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(94 citation statements)
references
References 99 publications
2
74
0
Order By: Relevance
“…The acidophiles were further grouped into nine clades, of which two represented different genera (clades 2 and 3); meanwhile, clades 4–10 grouped species from the Acidithiobacillus genus, which is divided into clades according to their capacity to obtain energy such as sulfur oxidizers (clades 4 and 5) and iron/sulfur oxidizers (clades 6–10). While the association between the Acidithiobacillaceae and Thermithiobacillaceae families was consistent with previous analyses ( Williams et al, 2010 ; Williams and Kelly, 2013 ; Boden et al, 2016 ; Moya-Beltrán et al, 2021 ), the tree also suggested a need for deeper phylogenomic analysis such as for the Acidithiobacillus clade, questioning if this clade includes more than a single genus according to their energy properties. Representative genomes from the ten clades of the core tree were selected for this study with their accession numbers and isolation data summarized in Table 1 .…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The acidophiles were further grouped into nine clades, of which two represented different genera (clades 2 and 3); meanwhile, clades 4–10 grouped species from the Acidithiobacillus genus, which is divided into clades according to their capacity to obtain energy such as sulfur oxidizers (clades 4 and 5) and iron/sulfur oxidizers (clades 6–10). While the association between the Acidithiobacillaceae and Thermithiobacillaceae families was consistent with previous analyses ( Williams et al, 2010 ; Williams and Kelly, 2013 ; Boden et al, 2016 ; Moya-Beltrán et al, 2021 ), the tree also suggested a need for deeper phylogenomic analysis such as for the Acidithiobacillus clade, questioning if this clade includes more than a single genus according to their energy properties. Representative genomes from the ten clades of the core tree were selected for this study with their accession numbers and isolation data summarized in Table 1 .…”
Section: Resultssupporting
confidence: 87%
“…Due to their acidophilic nature, the Acidithiobacillaceae are largely recalcitrant to standard genetic manipulation ( Inaba et al, 2018 ; Jung et al, 2021 ), and consequently, the use of bioinformatics approaches advances our understanding of the biology of these extremophiles. The research of Moya-Beltrán et al (2021) describes four Acidithiobacillaceae genera ( Nuñez et al, 2016 ), namely, (i) sulfur oxidizing Ambacidithiobacillus that includes the recently described species Am. sulfuriphilus (ex Acidithiobacillus sulfuriphilus ) ( Falagán et al, 2019 ); (ii) Igneacidithiobacillus including species I. copahuensis ( Moya-Beltrán et al, 2021 ), Candidatus I. taiwanensis ( Moya-Beltrán et al, 2021 ), and Candidatus I. yellowstonensis ( Moya-Beltrán et al, 2021 ); (iii) Fervidacidithiobacillus with F. caldus (ex- Acidithiobacillus caldus ) ( Hallberg and Lindström, 1994 ; Valdes et al, 2009 ; You et al, 2011 ; Zhang et al, 2016b ); and (iv) the Acidithiobacillus genus formed by A. thiooxidans ( Waksman and Joffe, 1922 ; Valdes et al, 2011 ; Travisany et al, 2014 ; Yin et al, 2014 ; Zhang et al, 2016a , 2018 ; Quatrini et al, 2017 ; Camacho et al, 2020 ), A. albertensis ( Bryant et al, 1983 ; Castro et al, 2017 ), Acidithiobacillus sp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…sulfidivorans T , and At. caldus strain BRGM3 ( Moya-Beltrán et al, 2021 ). Cultures were sourced from the Acidophile Culture Collection maintained at Bangor University except for the Acidianus species which were obtained from the German Collection of Microorganisms and Cell Cultures (DSMZ, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…A. ferrooxidans YNTRS-40, ATCC 23270, ATCC 53993 YQH-1 [9] CCM 4253, DSM 16786 [10], Hel18, PQ506 [10], PQ505 [10], CF3 [10], F221, BY0502, RVS1, DLC-5 [11], COP1 [10], S10 [10], BY-3 [12], ATCC 8085 [10], ZBY, DMC [12], A02 [12], Licanantay [13], JYC-17 [12], ATCC 15494 [10], BY-02 [12], A01 [14] A. caldus MTH-04, ATCC 51756 [15], SM-1 [16] KU [10], CV18-1 [10], 6 [10], MELC5 [10], BC13 [10], VAN18-3 [10], DX [17], ZBY [17], ZJ [17], MNG [10], C-SH12 [10], F [10], S1 [17] L. ferrooxidans C2-3 [18] L. ferriphilum ML-04 [19], YSK [20] UBA6657 [21], UBA5695 [21], UBA6673 [21], UBA6674 [21], UBA7872 [21], UBA7391 [21], UBA7384 [21], UBA7870 [21], UBA7392 [21], UBA6677 [21] DSM 14647 [22], pb_238, DX…”
Section: Complete Genome Scaffold Contigmentioning
confidence: 99%